NIMG-94. FEASIBILITY OF PROTON MRS FOR ASSESSING CEREBRAL METABOLIC ACTIVITY OF AN ATKINS-BASED DIET IN PATIENTS WITH GLIOMA - Schreck, Karisa C (Neuro Oncol, 2017)
INTRODUCTION: There is renewed interest in exploring treatment strategies which target metabolic pathways involved in gliomagenesis, including ketogenic diets. The purpose of this pilot study was to evaluate the feasibility of proton MR spectroscopy (MRS) to detect the cerebral metabolic activity of an 8-week GLioma Atkins-based Diet (GLAD) in patients with glioma. METHODS: Patients with grade 3-4 astrocytoma were enrolled after completing adjuvant chemotherapy, before first recurrence. GLAD consisted of 20gm carbohydrate restriction (modified Atkins diet) along with 2 days per week of intermittent fasting (caloric restriction to 20% recommended daily allowance). MRS was performed in both the lesion and a mirror voxel in the contralateral hemisphere at baseline and week 8. Data were analyzed using the ‘LCModel’ program using a basis set of three ketone bodies (acetone (Ace), beta-hydroxybutyrate (BHB), acetoacetate (AcAc)), 2-hydroxyglutarate (2-HG), citrate (Cit), and some standard metabolites. RESULTS: Interim analysis is reported after 12 patients enrolled; mean age 49 ± 11 years; 8 male; 5 grade IV astrocytomas. Two patients did not complete the study; two were excluded for incomplete data. As expected, concentrations of tNAA (p<0.028) and Lac (p<0.023) were different between lesion and normal brain at baseline. Ketone body concentrations were nearly undetectable at baseline; however by week 8, Ace and BHB were reliably detected in both lesion ([Ace]=0.08->0.32 ± 0.19, p=0.005; [BHB]=0.07->0.6 ± 0.68, p=0.05) and contralateral brain ([Ace]=0.01->0.16 ± 0.14, p=0.015; [BHB]=0->0.23 ± 0.25, p=0.021). In the lesion, BHB rose by 1.0mM from baseline to Week 8 in IDH1 mutant as compared to a decrease by -0.13mM in wild-type astrocytomas (p<0.002). The increase in BHB but not Ace was also significantly greater in patients with higher dietary compliance as measured by urine ketones (p<0.03). DISCUSSION: These preliminary results demonstrate the ability of brain MRS to monitor the metabolic consequences of a ketogenic diet in patients with high-grade glioma.